OPTIMIZING SUPPLY CHAIN PERFORMANCE THROUGH EFFECTIVE MARKETING AND LOGISTICS COORDINATION - Mishra, Krishna Kumar; Singh, Chandan; Mukherjee, Kausik; Soni, Kartik (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Optimizing supply chain performance has become increasingly critical in today's competitive global market. This paper investigates the synergistic effects of effective marketing and logistics coordination on supply chain performance. The study proposes a conceptual framework that integrates marketing strategies and logistical operations to enhance efficiency, responsiveness, and overall performance metrics within supply chains. By analyzing case studies and empirical data, this research demonstrates how coordinated efforts between marketing and logistics can lead to improved inventory management, reduced lead times, enhanced customer satisfaction, and increased profitability. The findings underscore the strategic importance of aligning marketing initiatives with logistics operations to achieve sustainable competitive advantage and operational excellence in supply chain management.